Computational studies of acetylcholinesterase complexed with fullerene derivatives: a new insight for Alzheimer disease treatment - da Silva Gonçalves, Arlan; França, Tanos Celmar Costa; Vital de Oliveira, Osmair (Journal of biomolecular structure & dynamics, 2016)
Here, we propose five fullerene (C60) derivatives as new drugs against Alzheimer's disease (AD). These compounds were designed to act as new human acetylcholinesterase (HssAChE) inhibitors by blocking its fasciculin II (FASII) binding site. Docking and molecular dynamic results show that our proposals bind to the HssAChE tunnel entrance, forming stable complex, and further binding free energy calculations suggest that three of the derivatives proposed here could be potent HssAChE inhibitors. We found a region formed by a set of residues (Tyr72, Asp74, Trp286, Gln291, Tyr341, and Pro344) which can be further exploited in the drug design of new inhibitors of HssAChE based on C60 derivatives. Results presented here report for the first time by a new class of molecules that can become effective drugs against AD.
Keywords: molekulární konformace; Models, Molecular; Molecular Conformation; fullerene derivatives; theoretical methodologies; simulace molekulového dockingu; Protein Binding; Molecular Docking Simulation; docking; vazebná místa; Alzheimer’s disease; molekulární modely; Binding Sites; cholinesterasové inhibitory; Drug Design; simulace molekulární dynamiky; Fullerenes; Molecular Dynamics Simulation; Acetylcholinesterase; fullereny; AChE inhibition; vazba proteinů; racionální návrh léčiv; molecular modeling; acetylcholinesterasa; Cholinesterase Inhibitors